2020
DOI: 10.37349/etat.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Possible applications of salvianolic acid B against different cancers

Abstract: Cancer is the second death causing disease worldwide after cardiovascular abnormalities. The difficulty in treating tumor cells with more precise targeted interventions and recurrence of cancer after treatment may pose great difficulty in developing sustainable therapeutic regimens. These limitations have prompted the need to explore several compounds with ability to cease tumor growth while at the same time induce apoptosis of tumor cells. Several studies have emphasized the use of natural compounds as antitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 161 publications
0
5
0
Order By: Relevance
“…Danshen, a traditional Chinese medicine, contains SAB, which pharmacological studies have identified as having antioxidative, anti-inflammatory, autophagy-promoting, anti-fibrotic, and angiogenic properties. 11 These attributes suggest that SAB could potentially enhance hair growth and mitigate hair loss. However, its role in protecting hair follicles from oxidative stress remains under-explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Danshen, a traditional Chinese medicine, contains SAB, which pharmacological studies have identified as having antioxidative, anti-inflammatory, autophagy-promoting, anti-fibrotic, and angiogenic properties. 11 These attributes suggest that SAB could potentially enhance hair growth and mitigate hair loss. However, its role in protecting hair follicles from oxidative stress remains under-explored.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting our observations, several studies have documented SAB's antitumor efficacy, highlighting its role in growth inhibition and apoptosis across various tumor cell types. 8,11,16 Studies indicate that environmental stressors like hydrogen peroxide (H2O2), ultraviolet radiation, and DHT contribute to damage in dermal papilla cells (DPCs), ultimately leading to hair loss. SAB demonstrates a protective effect against oxidative stress-induced damage in hair follicle cells, effectively maintaining hair growth promoters amidst these stress factors.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that different parts and different components of S. miltiorrhiza have effects against different types of non-small cell lung cancer (NSCLC) and the same component against the same type of lung cancer cells may involve multiple mechanisms of action, such as inhibiting cell proliferation, promoting cell apoptosis, inducing cell autophagy, regulating immune-related, fighting tumor angiogenesis and inhibiting cell migration and invasion ( 47 , 49 , 52 , 53 ) ( Fig. 2 ).…”
Section: Mechanisms Of Active Ingredients Of Salvia Miltior...mentioning
confidence: 99%
“…A naturally occurring phenolic substance with antioxidant effects is salvianolic acid B (SAB). On the other hand, the limited applicability of hydrophilic SAB may be due to its low bioavailability [ 244 ]. Boronic ester-based NPs can act as ROS-responsive vehicles that can quickly and selectively release drugs at the site of injured tissue [ 18 ].…”
Section: Peripheral Vascular Disease (Pvd)mentioning
confidence: 99%